Angelologia w "Listach" św. Ambrożego z Mediolanu - Czyżewski, Bogdan Stanisław (Vox Patrum, 2023)
In the letters of St. Ambrose of Milan, one can find many interesting theological topics, including motifs related to angelology. According to the bishop, angels were sent by God. They serve God and people, if only for the reason that man is the most important work of the Creator. Angels play an important role as guardians and protectors of people. Although the angelology contained in the letters of the Bishop of Milan is not one of his key topics, it reveals how he perceived the world of angels.